Scandinavian countries’ perspectives on low-carbon industry transition - Axelsson, Pontus; Blomberg, Jonathan; Flory Kjellin, Karolina; Lundskog, Marcus (My University, 2022)
This thesis examines the relationship between industry structures and low-carbon energy transition in the Scandinavian countries. The thesis is sorting out the most carbon intensive industries in Scandinavia and then analyzing the energy mixes the industries use in order to operate. The selected industries the thesis proceeds to analyze were the steel manufacturing industry the cement manufacturing industry and the refining of petroleum products. In order to grasp the energy use and supply of the chosen industries, different reference energy systems (RES) where established for the three different countries, which was the main methodology for this thesis. The RES provides an overview of the energy mixes of the energy supply and demand of the chosen industries. One of the main findings were that most of the emissions in the steel and cement industry occur in the chemical processes, while the largest source of emissions in the refining industry came from the combustion of natural and refinery gas. The next phase of the thesis provides results regarding new technologies for the industries that allows them to operate without emitting any greenhouse gases (GHG). The thesis argues that the refining industry will be converted into bio refining, making solely bio fuels. Regarding the steel industry it was found that hydrogen could be used as an reducing agent instead of using cok which allowed them to reach zero emissions. For the cement manufacturing industry a plasma technology in combination with carbon capturing and storage would allow the industry to reach zeros emissions. Although this technologies where found to be the most reasonable to utilize in the future, the cost is a huge increase in demand for green electricity. This is shown in a RES diagram which illustrates the energy flows in the energy systems for the studied countries and industries for 2050. The findings shows that the demand for green electricity and bio mass will rapidly increase in 2050. Furthermore, the biggest challenges lies within the expansion of wind power that will provide the new industry technologies with green electricity. Another challenge for the future energy system is the supply of bio mass, which will take the role of fossil fuels in 2050.
Keywords: Decarbonization; Industry; Scandinavia; Wind power; Bio mass; Reference energy system